Coaching-Based Self-Evaluation for Improving the Performance of Agricultural Extension Workers in the YESS Program in East Java - Gunawan; Harun, M Sazali; Dewi, Aisy Karima (Jurnal Penyuluhan, 2025)
Agriculture remains a strategic sector in Indonesia, providing food and substantial employment. However, the effectiveness of agricultural extension services is often limited by weak evaluation practices, which tend to function only as administrative routines. This study analyzes the implementation of self-evaluation among agricultural extension agents and examines the effectiveness of coaching in strengthening their competencies within BDSP areas of East Java. A Practical Action Research approach using mixed methods was applied, involving 48 extension agents (22 civil servants and 26 contract staff). Data were gathered through interviews, observations, FGDs, documentation, and pre–post assessments, and analyzed using thematic qualitative and descriptive quantitative techniques. Findings show substantial improvement in cognitive understanding (from 36% to 82%), practical skills (80%), and professional attitudes (78%) after the coaching intervention. The performance gap between civil servants and contract-based agents in evaluation practices also narrowed. These results demonstrate that coaching enhances both technical capacity and reflective awareness of evaluation as a tool for improving extension quality. The study reinforces the relevance of Rogers’ Diffusion of Innovations theory in agricultural extension and offers practical implications for developing participatory evaluation guidelines, continuous training, and inclusive policies for all extension personnel.